In Situ Microfocus Chemical Computed Tomography of the Composition of a Single Catalyst Particle During Hydrogenation of Nitrobenzene in the Liquid Phase1. Issue 34 (3rd July 2015) - Price, Stephen W. T.; Geraki, Kalotina; Ignatyev, Konstantin; Witte, Peter T.; Beale, Andrew M.; Mosselmans, J. Fred W.
Abstract Heterogeneous catalysis performed in the liquid phase is an important type of catalytic process which is rarely studied in situ. Using microfocus X‐ray fluorescence and X‐ray diffraction computed tomography (μ‐XRF‐CT, μ‐XRD‐CT) in combination with X‐ray absorption near‐edge spectroscopy (XANES), we have determined the active state of a Mo‐promoted Pt/C catalyst (NanoSelect) for the liquid‐phase hydrogenation of nitrobenzene under standard operating conditions. First, μ‐XRF‐CT and μ‐XRD‐CT reveal the active state of Pt catalyst to be reduced, noncrystalline, and evenly dispersed across the support surface. Second, imaging of the Pt and Mo distribution reveals they are highly stable on the support and not prone to leaching during the reaction. This study demonstrates the ability of chemical computed tomography to image the nature and spatial distribution of catalysts under reaction conditions.